Haemoglobin saturation during incremental arm and leg exercise. Issue 3 (September 1984) - Powers, S. K.; Dodd, S.; Woodyard, J.; Beadle, R. E.; Church, G.
Abstract : There are few reports concerning the alterations in the percent of haemoglobin saturated with oxygen (%SO2) during non-steady state incremental exercise. Further, no data exist to describe the %SO2 changes during arm exercise. Therefore, the purpose of this study was made to assess the dynamic changes in %SO2 during incremental arm and leg work. Nine trained subjects (7 males and 2 females) performed incremental arm and leg exercise to exhaustion on an arm crank ergometer and a cycle ergometer, respectively. Ventilation and gas exchange measurements were obtained minute by minute via open circuit spirometry and changes in %SO2 were recorded via an ear oximeter. No significant difference (p greater than 0.05) existed between arm and leg work in end-tidal oxygen (PETO2), end-tidal carbon dioxide (PETCO2), or %SO2 when compared as a function of percent VO2 max. These results provide evidence that arterial O2 desaturation occurs in a similar fashion in both incremental arm and leg work with the greatest changes in %SO2 occurring at work rates greater than 70% VO2 max.